Eucalyptus pests and diseases: Report of a meeting, 9-12 October 1995, Bangkok, Thailand - Diekmann, M.; Ball, J.B.; Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (1996)
This meeting was funded by ACIAR, and held at the ASEAN Forest Tree Seed Centre (AFTSC) at Saraburi, Thailand; FAO contributed to the printing costs of these proceedings, which contain a Report on the IPGRI/FAO Expert Meeting on Guidelines for the Safe Movement of Eucalyptus Germplasm, and 3 background papers: (1) IPGRI's Programme on Forest Genetic Resources and the Importance of Tree Germplasm Movement (Ouedraogo, A. S.); (2) International social and economic importance of Australian eucalypts (Vercoe, T. K,); and (3) The role of the Australian Tree Seed Centre in movement of Eucalyptus germplasm (Vercoe, T.; Midgley, S.). A list of participants and an agenda are also included. (Abstract © CAB ABSTRACTS, CAB International)